God's grace from ground zero : seeking God's heart for the future of our world - Cymbala, Jim, 1943-; Sorenson, Stephen (Grand Rapids, Mich. : Zondervan, 2001)
Offers spiritual guidance for finding hope in the midst of grief after the tragedy of the September 11th terrorist attacks.
Keywords: Terrorism -- Religious aspects -- Christianity; September 11 Terrorist Attacks, 2001 -- Religious aspects -- Christianity; Brooklyn Tabernacle (New York, N.Y.)